Circ_KIAA1199 inhibits MSI1 degradation by targeting miR-34c-5p to drive the malignant cell behaviors and tumor growth of colorectal cancer - Zhang, Yanbo; Yu, Hailong; Guo, Zhen (Anti-cancer drugs, 2022)
Circular RNAs (circRNAs) are important regulators that drive or inhibit cancer initiation and development. Here, we identified the expression and function of a circRNA, circ_KIAA1199, in colorectal cancer (CRC). The expression levels of circ_KIAA1199, microRNA-34c-5p (miR-34c-5p) and Musashi RNA-binding protein 1 (MSI1) mRNA were detected by quantitative real-time PCR. Cell proliferative capacity was assessed by colony formation assay, EdU assay and MTT assay. Cell apoptosis was determined by flow cytometry assay. Cell migration and cell invasion were investigated by transwell assay. The expression of MSI1 protein and proliferation, migration-related markers was detected by western blot. The relationship between miR-34c-5p and circ_KIAA1199 or MSI1 was verified by dual-luciferase reporter assay. Animal models were constructed to ascertain the role of circ_KIAA1199 in vivo. The expression of circ_KIAA1199 was elevated in CRC. Circ_KIAA1199 downregulation suppressed CRC cell proliferation, survival, migration and invasion. MiR-34c-5p was a target of circ_KIAA1199. The effects of circ_KIAA1199 downregulation were reversed by miR-34c-5p deficiency. In addition, MSI1 was a target of circ_KIAA1199, and the inhibitory effects of miR-34c-5p restoration on CRC cell proliferation, survival, migration and invasion were reversed by MSI1 overexpression. Circ_KIAA1199 positively regulated MSI1 expression by targeting miR-34c-5p. Moreover, circ_KIAA1199 knockdown blocked tumor growth in animal models. Circ_KIAA1199 functioned as an oncogene to drive the malignant development of CRC by activating MSI1 via competitively targeting miR-34c-5p.